World politics since 1989 - Holslag, Jonathan (Polity Press, 2021)
1989 ushered in a new age of freedom and prosperity. Thirty years later, the golden era is over. What went wrong? How did the age of globalization - of growing connectivity, affluence, and growth - give way? Jonathan Holslag navigates through the calm seas and rip tides of global politics from the Cold War to Russia's invasion of Ukraine. He tells a story of faltering momentum and squandered opportunities that explains how the West's sources of strength were lost to rising consumerism, unbalanced trade, and half-hearted diplomatic engagement. All the while, other powers, like China and Russia, grew stronger. With his trademark verve, Holslag untangles the threads of this story to reveal that it was not so much the ambition of China, the cunning of Putin, or the greed of African strongmen that led the world into this dark place; it was the failure of the West to listen to its people, to show clear leadership, and reinvent itself, in spite of ample evidence that things were going awry.